Implementation Strategies for Modular Construction Systems in Developing Countries: Perspectives of Nigerian AEC Professionals - Bello, Abdulkabir Opeyemi; Ihedigbo, Kingsley Sunday; Bello, Taofiq; Awwal, Hamzat Mohammed (Journal of Sustainability and Environmental Management, 2023)
This study aimed to develop effective strategies for implementing Modular Construction Systems (MCS) in developing countries, with a specific focus on the perspectives of Nigerian Architecture, Engineering, and Construction (AEC) professionals. A quantitative research approach was adopted, involving a survey of 227 AEC professionals in Nigeria. The survey collected respondents' perceptions on the developed MCS strategies in developing countries using a structured five-point Likert scale questionnaire. The professionals were identified through a snowball sampling technique. The results indicated that all fourteen hypothesized strategies were statistically significant for implementing MCS in developing countries. The strategies that received the highest mean scores were "Increasing awareness among professionals and stakeholders," "Creating an enabling environment within the industry," and "Government participation in the usage of MCS." The Kruskal-Wallis test revealed that professionals, regardless of their varied professions, held similar opinions on the identified strategies. The study has practical implications for the AEC industry in developing countries by providing valuable insights into strategies for implementing MCS. It can also assist policymakers in making informed decisions. Overall, this study offers a pathway for implementing MCS, addressing the housing shortage, and improving the quality of housing in developing countries.